2023
DOI: 10.1021/acs.jafc.3c00399
|View full text |Cite
|
Sign up to set email alerts
|

Cysteamine and N-Acetyl-cysteine Alleviate Placental Oxidative Stress and Barrier Function Damage Induced by Deoxynivalenol

Abstract: Sows are highly sensitive to deoxynivalenol (DON) and susceptible to reproductive toxicity caused by oxidative stress, but the potential mechanisms and effective interventions remain unclear. Here, we investigated the role of two antioxidants (cysteamine and N-acetyl-cysteine) in regulating the reproductive performance, redox status, and placental barrier function of sows and their potential mechanisms under DON exposure. Maternal dietary supply of antioxidants from day 85 of gestation to parturition reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…Generally, the distribution of DON was related to the target organ damage, so we further measured DON levels in different tissues of mice and found that DON was highly enriched in the placenta, and it was also detected in fetal tissues. This was consistent with the previous results of DON in different species, , suggesting that DON could be transported from the maternal side to the fetal side through the placenta, ultimately affecting fetal development. The DON-caused adverse pregnancy outcomes and embryotoxicity can be inferred to be related to placental function impairment.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Generally, the distribution of DON was related to the target organ damage, so we further measured DON levels in different tissues of mice and found that DON was highly enriched in the placenta, and it was also detected in fetal tissues. This was consistent with the previous results of DON in different species, , suggesting that DON could be transported from the maternal side to the fetal side through the placenta, ultimately affecting fetal development. The DON-caused adverse pregnancy outcomes and embryotoxicity can be inferred to be related to placental function impairment.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, DON-induced adverse pregnancy outcomes and embryonic development impairment were in line with other and our previous studies, indicating that DON could induce embryotoxicity and reproductive toxicity. , Compared with previous studies, the present experiment examined placental efficiency and the IUGR rate. Notably, placental efficiency, the grams of fetus produced per gram of placenta, was originally studied between swine breeds as a key factor in efficient nutrient exchange .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations